2015
DOI: 10.4236/odem.2015.32004
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact of Pesticides on Residents and Horticultural Workers in the Lake Naivasha Region, Kenya

Abstract: The horticultural sector has undergone tremendous growth in Kenya and is now the second largest foreign income earning sector in the country. Lake Naivasha is the hub of large scale horticultural farming in Kenya. This growth coupled with increased use of pesticides, may increase the possibility of pesticide exposure and its associated risks to workers and residents of the region. The purpose of this study was to assess the symptoms commonly experienced by residents of Naivasha town and their possible associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…To foster positive attitudes towards IPM and improve its eventual implementation and adoption, there is need for awareness campaigns along the whole chain of stakeholders, alongside regular farmer trainings. As part of the reinforcement, it may also be beneficial if governments could feed eco-toxicological data into national pesticide registration policies to improve the adoption of IPM through the enforced use of softer and safer insecticides [43,62].…”
Section: Poor Understanding Of the Ipm Concept And Information Flow Amentioning
confidence: 99%
See 1 more Smart Citation
“…To foster positive attitudes towards IPM and improve its eventual implementation and adoption, there is need for awareness campaigns along the whole chain of stakeholders, alongside regular farmer trainings. As part of the reinforcement, it may also be beneficial if governments could feed eco-toxicological data into national pesticide registration policies to improve the adoption of IPM through the enforced use of softer and safer insecticides [43,62].…”
Section: Poor Understanding Of the Ipm Concept And Information Flow Amentioning
confidence: 99%
“…This might result in unknown phytotoxicity and unwanted (and seldom known) chemical reactions into compounds, which are possibly more hazardous and persistent in the environment [61]. Such hazardous compounds, even when geographically concentrated in pattern, could create significant exposure to the environment and the public through non-occupational exposure, where individuals not directly involved with chemical use get exposed to the chemical hazards through a contaminated environment [61,62]. Magauzi et al [63] and Macharia et al [28] detailed pesticide-related illnesses in Zimbabwe and Kenya respectively, and it has been reported that various symptoms related to pesticide poisoning have significantly increased as most small-scale farmers misuse chemicals and do not use personal protective equipment (PPE) [64].…”
Section: Farmers' Behaviour and Insecticide Usementioning
confidence: 99%
“…1). At the same time, horticulture in East Africa is undergoing a tremendous development, and in Kenya the recorded pesticide use in 2005 was 7047 metric tonnes, with insecticides accounting for 40% of the total (Tsimbiri et al 2015). Similar trends in pesticide use have been reported in Tanzania (PAN-UK 2006).…”
Section: Agricultural Intensification and Pesticide Use In Ethiopia Asupporting
confidence: 61%
“…Agrochemicals entail a high risk of occupational pesticide exposure and environmental contamination, and serious poisoning problems and chronic illnesses result from pesticide exposure among agriculture workers [169]. Another problem is that the leaching of agrochemicals used in conventional agriculture systems (such as Glyphosate ((N phosphonomethyl) glycine) seems to be mainly determined by the soil structure and rainfall [170].…”
Section: Harm and Risks Of Agrochemical Use In Tropical Agrosystemsmentioning
confidence: 99%